Antibacterial Effectiveness of Seaweed (Eucheuma cottonii) Extract with Different Solvent - Muhammad Fahrul; Ira Sari; Dian Iriani (JURNAL AGROINDUSTRI HALAL, 2021)
This research was aims to determine the antibacterial characteristics of seaweed extract Eucheuma cottonii with different solvents against bacteria Bacillus cereus and Salmonella typhi, to determine the diameter of the inhibition zone and the minimum inhibition concentration of Bacillus cereus and Salmonella typhi bacteria. The research method used was an experimental method by extraction of Eucheuma cottonii with different solvents, namely ethanol 96% and hexane. The analysis parameters consisted of phytochemical identification tested, antibacterial tested, inhibition zone diameter, and minimum inhibition concentration. The results showed that E. cottonii seaweed extracted with ethanol 96% had of yield 3.16% and hexane 2.19%. The results of the phytochemical identification test (qualitative) showed a positive presence of phenolic compounds, steroids/triterpenoids, flavonoids, saponins. Both extractions are classified as having antibacterial activity against Bacillus cereus and Salmonella typhi bacteria. The 6% concentration of ethanol 96% solvent was the most effective in inhibiting the growth of Bacillus cereus bacteria with 7.33 mm of inhibition zone diameter. Meanwhile, the 4% concentration of ethanol 96% solvent was the most effective in inhibiting the growth of Salmonella typhi bacteria with 5 mm of inhibition zone diameter. Antibacterial from seaweed (Eucheuma cottonii) extracted with ethanol 96% and hexane solvent tends to be more effective in inhibiting the growth of Bacillus cereus bacteria than bacteria Salmonella typhi.Keywords: Eucheuma cottonii, Ethanol, Hexane, Antibacterial